Life and death on the Nile : a bioethnography of three ancient Nubian communities - Armelagos, George J.; Van Gerven, Dennis P. (University Press of Florida, 2017)
George J. Armelagos spent thirty years at various sites in Sudan searching for ancient Nubian civilizations that gave rise to what we now know as the upper Nile civilizations. Most of these sites are now underwater, due to being inundated when the Aswan Dam was built on the Upper Nile and flooded the ancient cities of Wadi Halfa and Kulubnarti. While hundreds of articles have been written about the research at these sites, this monograph, where Armelagos invited his former student Dennis Van Gerven to collaborate with him, represents the first attempt to explore all of the biocultural relationships between the villages, the people, and the region.